Correlation of Ambient Temperature With Feedlot Cattle Morbidity and Mortality in the Texas Panhandle - Broadway, Paul R.; Mauget, Steven A.; Burdick Sanchez, Nicole C.; Carroll, Jeffery A. (Frontiers in Veterinary Science, 2020)
Anecdotal data would suggest that weather patterns influence beef cattle health in feedyards, and cattle producers often associate the seasonality of some illnesses with changes in environmental temperatures. However, to our knowledge, there is little information from large-scale feeding operations and precision weather stations that establishes a link or lack thereof between weather patterns and cattle health. Additionally, we are unaware of any studies correlating other weather parameters with animal health data. Therefore, the objective of this study was to test for associations between monthly temperature variation and animal morbidity/mortality in feedlots in the Texas Panhandle. Weather data was collected from a Texas Tech University Mesonet weather station in close proximity to 19 beef cattle feedyards in the Texas Panhandle. Additionally, near real-time morbidity and mortality data was collected from those yards from 2015 to 2018. These data document a seasonal pattern relative to cattle morbidity and mortality with most health events occurring from November to January. This pattern is differentiated when comparing morbidity and mortality by listed causation (e.g., respiratory, digestive, other), and the majority of deaths over the entire time course were attributed to respiratory disease. Most cattle morbidity was documented in the winter months, most of which were classified as respiratory disorders. Additionally, an increase in health events was observed as the population of the feedyard increased. However, the overall effects of ambient temperature on cattle health were minimal and the two may not be causally linked. The initial overview of the relationships documented in this manuscript may warrant further stratification and exploration.